2008
DOI: 10.1152/ajpendo.00744.2007
|View full text |Cite
|
Sign up to set email alerts
|

The lowering of hepatic fatty acid uptake improves liver function and insulin sensitivity without affecting hepatic fat content in humans

Abstract: Iozzo P. The lowering of hepatic fatty acid uptake improves liver function and insulin sensitivity without affecting hepatic fat content in humans. Am J Physiol Endocrinol Metab 295: E413-E419, 2008. First published May 27, 2008 doi:10.1152/ajpendo.00744.2007.-Lipolysis may regulate liver free fatty acid (FFA) uptake and triglyceride accumulation; both are potential causes of insulin resistance and liver damage. We evaluated whether 1) systemic FFA release is the major determinant of liver FFA uptake in fasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 33 publications
(41 reference statements)
4
28
0
Order By: Relevance
“…The present evidence of increased TG content and release, paralleling the mounting HGU and hepatic glucose exposure over the course of the experiments in the absence of extra-hepatic FFA supply suggests an upregulation of de novo lipogenesis, in line with the notion that glucose entering glycolysis can be converted either in glycerol or in acetate for FFA synthesis to provide both structural components of the TG molecule. This reasoning is in accord with our previous observation in humans (21), in whom the acute inhibition of lipolysis was promptly followed by an elevation in liver acetate retention, suggesting the activation of de novo lipogenesis to compensate for FFA deprivation. In this study, the mechanism would be further promoted by the simultaneous provision of excess glucose substrate, which does not rule out that residual FFA delivery-though very small-may have been incorporated in TG.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present evidence of increased TG content and release, paralleling the mounting HGU and hepatic glucose exposure over the course of the experiments in the absence of extra-hepatic FFA supply suggests an upregulation of de novo lipogenesis, in line with the notion that glucose entering glycolysis can be converted either in glycerol or in acetate for FFA synthesis to provide both structural components of the TG molecule. This reasoning is in accord with our previous observation in humans (21), in whom the acute inhibition of lipolysis was promptly followed by an elevation in liver acetate retention, suggesting the activation of de novo lipogenesis to compensate for FFA deprivation. In this study, the mechanism would be further promoted by the simultaneous provision of excess glucose substrate, which does not rule out that residual FFA delivery-though very small-may have been incorporated in TG.…”
Section: Discussionsupporting
confidence: 92%
“…So far, studies in humans showing hyperglycemia-induced TG hypersecretion (20) have been conducted during FFA repletion, thus suggesting a diversion of FFA from the catabolic to the anabolic route. We have recently shown that liver FFA uptake relies primarily upon systemic lipolysis, and is very low at plasma FFA levels similar to the ones achieved during hyperglycemia in the current study (21). Consistent with the above concepts, results from our previous studies using PET in a similar animal model during euglycemic hyperinsulinemia (22), together with human studies evaluating the response to the antilipolytic agent acipimox (21), and splanchnic balance investigations in humans during hyperinsulinemia (3) suggested that FFA suppression, whether achieved by hyperinsulinemia or by acipimox inhibits liver TG output due to the lack of substrate.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The production of VLDL-TGs or liver-secreted TGs has been measured in several studies using tracer methodologies [9-11], and shown to be predominately regulated by the provision of plasma FFAs [12-14]. Under most conditions, the re-esterification of plasma FAs to TGs accounts for the majority of TGs synthesized in liver and the contribution of de novo synthesis of FAs to VLDL-TG production is minor [14].…”
Section: Introductionmentioning
confidence: 99%
“…Rapid intravenous injection of an FFA tracer is useful when aspects of nonoxidative FA metabolism are investigated. Examples include the incorporation of plasma FAs into VLDL-triglyceride (TG) ( 15,16 ) or the storage/uptake of plasma FAs into tissues (17)(18)(19)(20). In addition, intravenous injections can be more convenient than a continuous infusion, because bolus injections obviate the need to keep the volunteers connected to an infusion pump, thus offering greater mobility and freedom during experimental days.…”
mentioning
confidence: 99%